The legitimacy of Indonesian language in contract formation following Supreme Court Circular Letter Number 3 of 2023 - Inri Januar; Budi Santoso; Rachmi Sulistyarini; Siti Hamidah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to examine whether Indonesian legislation permits using foreign languages in contract drafting. It employs normative research methods with primary and secondary legal materials. The findings reveal a vertical normative conflict between lower and higher regulations, leading to differences in interpretation and creating legal uncertainty for parties in agreements. Using the Indonesian language in contracts is essential because it acts as one of the national symbols, compelling the state to mandate its use in agreements involving Indonesian citizens. However, in contracts, this requirement can be bypassed through the choice of law principle. In addition, the study addresses the "take it or leave it" concept in standard contracts, which often enforces the use of Indonesian without opportunities for negotiation. Moreover, it discusses the legal implications of drafting contracts in foreign languages, emphasizing the need for careful consideration to ensure compliance with Indonesian law.